Fast Wide‐Line Solid‐State NMR on a Low‐Cost Benchtop Spectrometer. Issue 22 (9th October 2018) - Sørensen, Morten K.; Balsgart, Nicholas M.; Jensen, Ole; Nielsen, Niels Chr.; Vosegaard, Thomas
Abstract: Solid‐state NMR may provide access to a wealth of information on molecular structure and dynamics. However, for many applications, the acquisition is challenged by broad resonances implying large spectral linewidths and low sensitivity. Conventionally, this is tackled by using costly and laboratory‐fixed spectrometers based on large high‐field superconducting magnets. In this Communication, we demonstrate that a range of challenging wide‐line solid‐state NMR spectra can be acquired on a robust, maintenance‐free, low‐cost benchtop/mobile NMR spectrometer with a sensitivity comparable to common high‐field instruments. The performance and versatility for recording sensitive wide‐line spectra is demonstrated through acquisition of 31 P NMR of paramagnetic FePO4 and full quadupolar lineshapes of Al2 O3 ( 27 Al) and KNO3 ( 14 N). Also, we introduce interleaved acquisition of frequency‐stepped slices providing a dramatic reduction of the required experiment time. Abstract : Solid‐state NMR made accessible : To enable a wider application of solid‐state NMR, the authors present the acquisition of challenging wide‐line spectra on a low‐cost, mobile, maintenance‐free, benchtop NMR instrument. Spectra are obtained quickly and with a sensitivity comparable to high‐field NMR, including a novel interleaved sample scheme for efficient frequency‐stepped acquisition.